2001
DOI: 10.1046/j.1365-313x.2001.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial expression patterns of a phosphate transporter (MtPT1) from Medicago truncatula indicate a role in phosphate transport at the root/soil interface

Abstract: SummaryThe movement of phosphate from the soil into plant root cells is the ®rst of many crucial transport events required to supply phosphorous (P) to cells throughout the plant. In addition to the ability to acquire phosphate from the soil, the majority of the vascular plants are able to form arbuscular mycorrhizal associations in which phosphate may be delivered to the cortex via a fungus. Previously, we cloned two phosphate transporter genes, MtPT1 and MtPT2 from Medicago truncatula roots. Complementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
146
1
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 48 publications
17
146
1
7
Order By: Relevance
“…Means followed by the same letter within columns are not significantly different by Duncan's multiple range test at the 5% level. downregulate high-affinity phosphate transporters (MtPT1 and MtPT2) which may be responsible for absorption of phosphate from soil by M. truncatula (Liu et al, 1998;Chiou et al, 2001;Burleigh, 2001). Furthermore, studies on the kinetics of phosphate/arsenate uptake have suggested that AMF can downregulate phosphate/arsenate transporters in both arsenate resistant and non-resistant Holcus lanatus (Gonzalez-Chavez et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Means followed by the same letter within columns are not significantly different by Duncan's multiple range test at the 5% level. downregulate high-affinity phosphate transporters (MtPT1 and MtPT2) which may be responsible for absorption of phosphate from soil by M. truncatula (Liu et al, 1998;Chiou et al, 2001;Burleigh, 2001). Furthermore, studies on the kinetics of phosphate/arsenate uptake have suggested that AMF can downregulate phosphate/arsenate transporters in both arsenate resistant and non-resistant Holcus lanatus (Gonzalez-Chavez et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The PM was purified essentially according to Rabotti and Zocchi (1994) and Chiou et al (2001). All steps were performed at 4°C.…”
Section: Preparation and Purity Of M Truncatula Pmmentioning
confidence: 99%
“…Similar to yeast PHO84, members of the PHT1 family are localized to the plasma membrane (Chiou et al, 2001;Shin et al, 2004). This indicates that the activity of Pi transporters is controlled through the secretory pathway trafficking to the plasma membrane.…”
mentioning
confidence: 91%